Fulvestrant for the treatment of advanced breast cancer - Blackburn, Sophie A.; Parks, Ruth M.; Cheung, Kwok-Leung (Taylor & Francis, 2018)
Introduction: The current issues with endocrine therapy for treatment of advanced breast cancer include balance of efficacy of therapy versus tolerability as well as hormone resistance. The efficacy of fulvestrant, a selective oestrogen receptor degrader (SERD), has been demonstrated in hormone receptor positive patients previously untreated or treated with hormonal therapy. Areas covered: This article discusses the journey of fulvestrant licensing, its efficacy in combination with other endocrine therapies and the future role it may have within breast cancer treatment. Expert commentary: Within phase III trials, fulvestrant has demonstrated equivalent or improved clinical efficacy when compared with established endocrine agents. In the recent decade, fulvestrant has achieved licensing as a second line agent in non-operative advanced breast cancer at initially 250mg, increasing to 500mg. Presently, fulvestrant is licensed globally as first line endocrine management for advanced breast cancer in post-menopausal women. Early combination trials of fulvestrant and cyclin dependent kinase 4/6 inhibitors have demonstrated good clinical efficacy with improved progression free survival when compared to fulvestrant alone.